Association between Body Mass Index and Vitamin D Serum in Asian Population: A Systematic Review - Suhartono, Janice; Astiarani, Yunisa; Regina (Public Health and Preventive Medicine Archive, 2022)
than other populations with the same body mass index (BMI). Fat accumulation is suspected of mediating the rise and fall of Vitamin D levels linked to BMI. However, the results of studies assessing the association between BMI and Vitamin D serum in Asian population still varied. This study is conducted to determine the association between BMI and vitamin D serum in the Asian population. Methods: This study was conducted with a systematic review method to identify scientific articles reporting the association between BMI and Vitamin D serum in the Asian population. The data collected for this systematic review were from 5,477 studies filtered with the inclusion and exclusion criteria, resulting in eleven studies presenting 7,496 respondents. Results: Nine studies concluded an association between increasing BMI from the normal range and decreasing Vitamin D serum (p<0,05). One study has concluded an association between decreasing BMI from the normal range and decreasing Vitamin D serum (p<0,05). Another has concluded there is no association between BMI and Vitamin D serum (p>0,05). Conclusion:This systematic review study concludes an association between increasing and decreasing BMI with decreasing Vitamin D serum in the Asian population. Further study using clinical trial in obese people and control to compare the metabolism of Vitamin D should be conducted.